Analisis Kebutuhan Petani Terhadap Mesin Tanam Padi Dalam Mendukung Asta Cita Swasembada Pangan di Indonesia - Prasnowo, M Adhi; Darno (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
The government has launched Asta Cita, one of its objectives being to strengthen the country's defense and security system and promote national independence through self-sufficiency in food, energy, and water, as well as in the creative, green, and blue economies. This Asta Cita program is very realistic, because the Indonesian people have extensive rice paddies planted. However, many young people now refuse to become farmers because it requires a lot of labor and is not profitable. Most rice cultivation carried out by farmers in Indonesia employs traditional planting methods that require a relatively large labor force, accounting for 25-30% of the total rice production workforce, thereby affecting national rice production. The availability of rice planting machines is not yet a solution, because the price of the machine is expensive and the seeds are too short, namely 10-15 cm in length, so that during planting, water must be removed until the planted seeds are around 20 cm tall. This causes grass to grow abundantly, because the rice seeds are not optimally irrigated. Therefore, research on the development of rice planting machines is urgently needed to support the Asta Cita food self-sufficiency in Indonesia. The purpose of this study is to design a rice planting machine according to the needs of farmers and land topography. This study uses the Quality Function Deployment (QFD) method because this method is very suitable for use in developing products that are in accordance with consumer expectations and desires. The results of this study indicate that farmers need rice planting machines that are affordable, fast, easy to maintain, lightweight, readily available for spare parts, reliable in all types of soil, ergonomic, 15 cm long, non-slip. Therefore, the development of rice planting machines is crucial to assist farmers in the rice planting process and support food self-sufficiency.